Testing the impact of interpersonal regulatory fit on empathy, helping intentions, and prosocial behaviour - Rinad Bakhti; Karl-Andrew Woltin; Kai Sassenberg; John Rae (PLoS ONE, 2022)
Similarity with others in need regarding various attributes [e.g., social group membership] has been shown to increase individuals’ empathic responses, willingness to help and prosocial behaviour. We tested whether a subtle similarity, namely of observers’ and targets’ self-regulatory orientation in terms of a promotion or prevention regulatory focus [i.e., interpersonal regulatory fit], would entail similar effects. Interpersonal regulatory [mis]fit was conveyed through focus-congruent or -incongruent emotional reactions which targets, facing distressing situations, expressed. We predicted that when observer participants’ regulatory focus fits with targets’ negative emotional reaction [i.e., promotion focus—dejection or prevention focus—agitation], they would be more likely to express empathy, willingness to help, and to engage in prosocial behaviour towards this target compared to conditions of misfit. Five studies relied on observers’ chronic regulatory focus [Study 1, 3, & 4] and situationally induced regulatory focus [Study 2 & 5] and presented different distressing scenarios with targets conveying focus [in]congruent negative emotions. Inconsistent results emerged across the studies, which indicated misfit, fit and no effects. Study characteristics did not suggest a moderator explaining these inconsistent findings. An internal meta-analysis across all studies indicated that overall there was no evidence of either a fit or a misfit effect. This work sheds light on the technical challenges of exploring relations between subtle interpersonal regulatory [mis]fit and prosocial reactions. Implications for future research are discussed, including the importance of creating stronger interpersonal [mis]fit experiences by means of incorporating descriptions of distressed targets’ hindered goal pursuits as well as negative reactions.